Tutela mulierum: The Institution of Guardianship over full Aged Women in the Late Roman Republic and Early Principate - Szabó, Mária (Acta Classica Universitatis Scientiarum Debreceniensis, 2020)
The purpose of this study is to examine the social and legal opportunities of the Roman women through the tutela mulierum in the late Republic and early Principate. The base of the disquisition is a remark in Gaius’ Institutes, which says that full aged women, in spite of being legally under guardianship, administer their own property. The examined sources show relevant social changes, which resulted in the guardians’ sanction becoming merely formal, yet indispensable condition for concluding certain transactions. Therefore the reason for retaining guardianship may be associated with the nature of these transactions. Women, who did often run enterprises on their own, did not have the authority to conclude the transactions of archaic law, based on the so-called „words of creation”, until the legislative reforms of the 4th century AD.